2005
DOI: 10.1111/j.1365-2265.2005.02350.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone on sexual function in men: results of a meta‐analysis

Abstract: Overall, 656 subjects were evaluated: 284 were randomized to T, 284 to placebo (P) and 88 treated in cross-over. The median study length was 3 months (range 1-36 months). Our meta-analysis showed that in men with an average T level at baseline below 12 nmol/l, T treatment moderately improved the number of nocturnal erections, sexual thoughts and motivation, number of successful intercourses, scores of erectile function and overall sexual satisfaction, whereas T had no effect on erectile function in eugonadal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
281
4
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(320 citation statements)
references
References 111 publications
25
281
4
5
Order By: Relevance
“…The patient should also meet the definition of ED [4]. [146] determined that exogenous testosterone improved the number of nocturnal erections and successful intercourses, sexual thoughts, scores of erectile function, and overall sexual satisfaction in men with low testosterone, but had no effect on eugonadal men. They concluded that the effect of testosterone tended to decline over time and was progressively smaller with increasing baseline T levels, and that long-term safety data were not available [146].…”
Section: Step Care 4: Hormonal and Nonhormonal Pharmacologic Treatmentmentioning
confidence: 99%
“…The patient should also meet the definition of ED [4]. [146] determined that exogenous testosterone improved the number of nocturnal erections and successful intercourses, sexual thoughts, scores of erectile function, and overall sexual satisfaction in men with low testosterone, but had no effect on eugonadal men. They concluded that the effect of testosterone tended to decline over time and was progressively smaller with increasing baseline T levels, and that long-term safety data were not available [146].…”
Section: Step Care 4: Hormonal and Nonhormonal Pharmacologic Treatmentmentioning
confidence: 99%
“…[86][87][88] Overviews of randomized controlled clinical trials indicate some benefit of testosterone therapy on sexual health-related outcomes, however further investigation in this area is warranted particularly in older men who are not clearly hypogonadal. 65,[88][89][90] In men with erectile dysfunction, low free testosterone levels correlate with impaired relaxation of cavernous endothelial and corporeal smooth muscle cells to a vasoactive challenge. 91 A direct effect of testosterone is feasible as testosterone modulates expression of endothelial nitric oxide synthase and phosphodiesterase type 5 (PDE5) within penile tissues.…”
Section: Testosterone and Sexual Health In Aging Menmentioning
confidence: 99%
“…TRT increases the activity of hepatic lipoprotein lipase inducing a decrease in high density lipoprotein levels [20], especially in patients with higher pretreatment T levels [99]. Intramuscular (IM) T has smaller effects on HDL, probably through higher conversion to E2 counteracting T effects on lipoprotein lipase [100].…”
Section: Cardiovascular Diseasementioning
confidence: 99%